Logistic Cost Analysis of Rice Straw to Optimize Power Plant in Malaysia - Shafie, Shafini; Mahlia, T.M.I.; Masjuki, H.H.; Chong, W.T. (Lifescience Global, 2013)
This paper presents a logistic cost analysis of rice-straw based power generation. Mathematical logistic models were developed to determine collection, storage and transportation costs of rice-straw based power generation. The optimization technique was used to identify the location of power plant and optimum number of storage facilities. The results indicated that transportation costs were the highest of the logistic costs, contributing 54% to 63% of the total logistic costs and that transportation of rice straw to collection centres contributed 89.9% of the total transportation costs due to effect of truck capacity. Reduction in the number of storage facilities would improve transportation cost